Unveiling new insights: a comprehensive questionnaire-based single-center study of sebaceous nevus - Jin, Jiamin; Dai, Tao; An, Lu; Lai, Bohan; Gu, Jieyu; Wei, Boxuan; Wang, Shen; Xie, Feng (Frontiers in Oncology, 2025)
IntroductionSebaceous nevus (SN) is a rare, benign, congenital tumor. There is limited information on its clinical features, familial influences, quality of life (QoL) impact, and treatment outcomes in Chinese patients. This study aimed to comprehensively examine these aspects.MethodsA questionnaire-based survey was conducted among patients with SN who visited the Department of Plastic Surgery at Shanghai Ninth People’s Hospital between January 2018 and December 2023. Healthy control children were recruited using the ‘best friends’ principle to assess familial influences. QoL impact was measured using the Children’s Dermatology Life Quality Index (CDLQI).ResultsOur analysis revealed that the severity of skin-related symptoms correlated with the extent of hyperplasia and lesion size. Maternal factors during pregnancy—including medication use, secondhand smoke exposure, toxic chemical contact, and illness (notably COVID-19 infection)—were significantly associated with a higher incidence of SN. Most patients reported a mild to moderate QoL impact. Surgical treatment demonstrated higher satisfaction rates compared to laser therapy.DiscussionThese findings suggest that hyperplasia and lesion size may predict symptom severity. The observed association between maternal COVID-19 infection and the occurrence of SN warrants further investigation. Surgical intervention appears to be an effective treatment, particularly for easily removable lesions.